Examining patient safety attitudes among urology trainees. (January 2014) - Geraghty, Alistair; Reid, Sarah; McIlhenny, Craig
Abstract : Objectives: To identify current attitudes to patient safety among urology trainees. To examine whether these have changed with the recent increase in emphasis on patient safety and the introduction of new working procedures in operating theatres. Subjects and Methods: Subjects included 28 urology trainees, based in the West of Scotland, UK. Trainee attitudes were examined using the Operating Room Management Attitudes Questionnaire, a validated tool for examining attitudes towards patient safety. Results: Attitudes to teamwork were highly positive, with 89–100% of trainees acknowledging the need to share information and conduct pre‐ and postoperative briefs, and 82–96% being accepting of multidisciplinary feedback on performance. Attitudes to preoperative briefing and multidisciplinary feedback were improved compared with a similar historical cohort. Trainees were reluctant to acknowledge the effect of stress and fatigue on personal performance; 50% felt they worked effectively in critical phases of operations even when tired, only 50% would tell team members their workload was becoming excessive and only 36% of trainees recognized that personal problems could affect their performance. There was no significant change in these attitudes from 2006 data. Regarding leadership and confidence assertion, 68% of trainees felt that leadership in the operating theatre should rest with the medical staff, 18% stated senior decisions or actions should not be questioned unless they threaten safety and 7% that they should not be questioned at all. This was similar to previous data. Conclusions: Attitudes to briefing and multidisciplinary feedback appear to have improved since the introduction of the World Health Organization surgical checklist and wider use of feedback tools; other safety attitudes remain largely unchanged. Urology trainees may benefit from further training to better understand the mechanisms of error development, to raise awareness of human performance limitation, particularly the effects of stress and fatigue, and to develop techniques to challenge decisions/respond to challenges.